Elite School Designation and House Prices - Quasi-experimental Evidence from Beijing, China - Bin Huang; Xiaoyan He; Lei Xu; Yu Zhu (Global Labor Organization (GLO), 2018)
We explore three recent comprehensive reforms which aim to equalize access to elite elementary schools in Beijing, to identify the causal effect of access to quality education on house prices. Using property transaction records from Beijing in 2013 and 2016, we construct a balanced panel of residential complexes, each of which linked to its designated primary school. Whereas the multi-school dicing reform involves randomly assigning previously ineligible pupils to key elementary schools through lotteries, the reform of school federation led by elite schools consolidates ordinary primary schools through alliance with elite schools. Moreover, an ordinary primary school can be promoted to key elementary school without involving neighbouring schools in surrounding residential complexes through a “pure” re-designation effect. We allow for systemic differences between the treated and non-treated residential complexes using the Matching Difference-in-Differences (MDID) approach. Our estimates indicate that the causal effect on house prices of being eligible to enrol in a municipal-level key primary school is about 5-7%, while the premium for being eligible for a less prestigious district-level key primary school is only about 1-3%.
Keywords: R21; I28; H44; 330; quality school designation; house price premium; Matching DID; China